2013
DOI: 10.1371/journal.pone.0053305
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a G:T Mispair on the Dynamics of DNA

Abstract: Distortions in the DNA sequence such as damages or mispairs are specifically recognized and processed by DNA repair enzymes. A particular challenge for the enzymatic specificity is the recognition of a wrongly-placed native nucleotide such as thymine in T:G mispairs. An important step of substrate binding which is observed in many repair proteins is the flipping of the target base out of the DNA helix into the enzyme’s active site. In this work we investigate how much the intrinsic dynamics of mispaired DNA is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 62 publications
8
44
3
Order By: Relevance
“…Extrahelical conformations form local minima separated from the principal minimum by activation barriers. Similar results have been reported in the literature for a subset of the base pairs considered in this study (30,46,47).…”
Section: Base Flipsupporting
confidence: 92%
See 2 more Smart Citations
“…Extrahelical conformations form local minima separated from the principal minimum by activation barriers. Similar results have been reported in the literature for a subset of the base pairs considered in this study (30,46,47).…”
Section: Base Flipsupporting
confidence: 92%
“…al. (30) observed a notable (∼10 • ) shift of the minimum from unbiased to biased simulation of the TG mismatched system. They hypothesize that the long timescale of flipping and re-stacking causes the free energy to converge slowly.…”
Section: Base Flipmentioning
confidence: 91%
See 1 more Smart Citation
“…Because, as discussed above, the base flipping is a slow process that is beyond the capability of normal molecular dynamics simulations, enhanced sampling techniques are needed. In most previous studies, the umbrella sampling method, for which a predefined reaction coordinate has to be taken, was applied to calculate the free-energy profile for base flipping and has yielded much important information (18,21,47,48). However, Song et al showed (48) that slightly different preselected reaction coordinates can lead to very different results.…”
Section: B) Melting Curves Of the T-t Mismatch (Red) C-t Mismatch (Gmentioning
confidence: 99%
“…The reaction coordinate for the base flip has been defined as a pseudo-dihedral angle between the flipping base, the sugar moiety of the same nucleotide, the sugar of the next nucleotide and the base of the next nucleotide, plus the base and sugar of the opposing nucleotide downstream (see Figure 8). This definition of the flipping coordinate is the same as we had used in an earlier study [14] and is similar to the one proposed and applied in [21,40,41]. The potential of mean force (free energy profile) was obtained by discretizing the reaction coordinate between 10° and 180° into windows of a 2° width, and in each window, 2000 samples were collected before the bias was applied.…”
Section: Methodsmentioning
confidence: 99%